Reducing and reusing industrial scraps: a proposed method for industrial designers. (1st January 2015) - Pacelli, Francesco; Ostuzzi, Francesca; Levi, Marinella
Abstract: Designers often develop products without a real vision of industrial dynamics, not taking into consideration how their choices can affect environmental and economical aspects of the product development process. Our research concentrates on industrial scraps. How can designers actively reduce scraps since early product development phase? To answer this, we firstly analyzed the existing norms within Italian and European jurisdiction and classified various case studies, where design was carried out taking into consideration industrial scraps. We then developed a method to be followed by products designers and companies, intended to help them obtaining both environmental and economical advantages by sustainable practices in an industrial context. The approach consists in a simplified procedural methodology that indicates all needed steps to design industrial products based on these practices. Finally we applied and verified the feasibility of this methodology on specific and original case studies. In our conclusions we summarize limits and advantages of the method and how designers and companies can develop new industrial products through this ecodesign approach, raising consciousness during the design process and giving the chance to achieve better economic and sustainable standards by applying the tool here developed. Graphical abstract: Highlights: Ecodesign practices lead to economic and environmental advantages. We discuss a design method to obtain products by reusing industrial scraps. We applied our method to original and existing industrial case studies. The method is applicable to large number of materials and manufacturing processes.